Security Considerations of Network Coding Algorithms in Wireless Systems - Lakshman, K; Kumar, Amit; Jain, Sandeep Kumar (International Conference on Computing, Communication, and Networking Technologies (Online), 2024)
Network coding is an emerging generation that offers a brand new technique to increase the performance of facts transmission in Wi-Fi networks. Community coding is the technique of encoding facts in such a manner that two or extra nodes can cooperate to create an unmarried, optimized statistics transmission. This generation is being explored to be used in WiFi networks to enhance throughput and balance. However, there are substantial security worries that ought to be addressed with a purpose to keep networks secure. The primary trouble with network coding is that it will increase the complexity of protection protocols. Because of the truth, the transmission of facts is being win-changed, and it turns into win-difficult to perceive malicious packets. Different protection problems result from the possibility of a malicious node tampering with community coding messages or intercepting them before they reach their holiday spot. This will result in a denial of provider assault or may also want to enable an attacker to manage the community. To deal with those security problems, researchers have proposed using diverse encryption strategies, collectively with symmetric-key cryptography or virtual signatures. These strategies should defend transmitted facts from malicious nodes while keeping the shape of network coding. Additionally, getting access to govern strategies can be employed to make sure that the most effective trusted nodes are allowed to alter messages or get entry to other resources in the community.